1982
DOI: 10.1007/bf00257725
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intensive dietary therapy on serum high density lipoprotein cholesterol in patients with type 2 (non-insulin-dependent) diabetes mellitus: A prospective study

Abstract: Summary. Intensive dietary therapy in 57 newly diagnosed Type 2 (non-insulin-dependent) diabetic patients led to an increase, compared with pre-treatment levels, in serum high density lipoprotein (HDL) cholesterol and the HDL/total cholesterol ratio after 3 and 6 months (0.05 < p < 0.1). The increase in HDL cholesterol was related to the degree of weight loss achieved. In 28 patients whose weight decreased by > 10% average body weight during the 6 months, HDL cholesterol rose from 1.22 + 0.06 to 1.36 + 0.06 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
(18 reference statements)
3
16
0
Order By: Relevance
“…Most workers have reported a complete lack of correlation between the duration of diabetes and the serum lipids. 9,10 The findings of the present study were similar except that, the triglycerides showed slight increase with increase in duration of diabetes. It was also found that all lipid fractions profoundly increased with increasing severity of diabetes.…”
Section: Discussionsupporting
confidence: 81%
“…Most workers have reported a complete lack of correlation between the duration of diabetes and the serum lipids. 9,10 The findings of the present study were similar except that, the triglycerides showed slight increase with increase in duration of diabetes. It was also found that all lipid fractions profoundly increased with increasing severity of diabetes.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors have reported impressive reductions in fasting plasma glucose and TG concentrations in response to weight reduction [175][176][177][178][179][180][181][182][183][184]. The fact that these beneficial metabolic effects already occurred after minor weight reduction while the majority of subjects remained overweight [179,180] emphasizes the therapeutic benefits of weight loss [185][186][187][188].…”
Section: Weight Loss and Dietmentioning
confidence: 99%
“…The fact that these beneficial metabolic effects already occurred after minor weight reduction while the majority of subjects remained overweight [179,180] emphasizes the therapeutic benefits of weight loss [185][186][187][188]. Although the effect of weight loss on plasma HDL-C levels is not as dramatic as the change in TG metabolism, modest improvements in HDL-C concentrations and HDL-C to LDL-C ratios are commonly observed [176,177]. Weisweiler et al [175] demonstrated that a hypocaloric diet did not only reduce VLDL-TG and apo B concentrations, but also beneficially changed the composition, as indicated by a decreased cholesterol content.…”
Section: Weight Loss and Dietmentioning
confidence: 99%
“…At 1 yr, however, plasma TG returned to pretreatment levels, despite persistent improvement in weight and serum glucose concentrations (92). On the other hand, when a weight reduction of 10% is maintained, a sustained improvement in plasma TG, HDL-chol, and HDL-chol to total cholesterol ratio is observed (93). Diabetic patients hospitalized and placed on hypocaloric diets demonstrate even more marked improvement in plasma lipoprotein concentrations.…”
Section: What Is Effect Of Antid1abetic Treatment On Plasma Lip1ds Anmentioning
confidence: 97%
“…Decreases in VLDL-TG were due to decreased synthesis in most patients because the VLDL removal rate and LPL activity were unchanged during a hypocaloric diet (95,96). In most studies, HDL-chol is usually increased in NIDDM when weight loss has been achieved (93,(96)(97)(98), although some investigators have reported no change (94). Treatment of NIDDM with sulfonylurea results in improved glycemic control and reduced TG concentrations (99)(100)(101)(102).…”
Section: What Is Effect Of Antid1abetic Treatment On Plasma Lip1ds Anmentioning
confidence: 99%